Thymoma Laporan Kasus Dengan Tinjauan Pustaka - Roekmini Soedibjo, Roekmini Soedibjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1985)
Three cases of thymoma were reported. Each was located in the anterior part of the media - stinum. The symptoms were dyspnea, cough, and increased blood pressure which possibly is caused by the pressure on the mediastinal organs by the tumor. In all cases either the macroscopic-or the microscopic examinations were benign. Histologically the tumor showed areas of epithelium cells and lymphocytes separated by connective tissues septum which were seen also in the gross picture. No invasive tumor was found in the surrounding tissues or organs. There was no myasthenia gravis found in all the three cases. Key Words: mediastinal pressures symptom - thymoma - tumor - thymus - lymphoma